Faktor-Faktor Yang Berhubungan dengan Kejadian Rawat Inap Ulang pada Pasien CHF di RSUD Dr. Gunawan Mangunkusumo - Devanda Ivo Teresia; Widodo, Gipta Galih; Ummu Muntamah; Zumrotul Chaerijah (Indonesian Journal of Nursing Research (IJNR), 2024)
CHF patients are often re-hospitalized due to recurrence causing despair and fear of death. Several factors that influence re-hospitalization are family support, adherence to medication therapy and adherence to a low-salt diet Objective: To determine the factors associated with the incidence of re-hospitalization in congestive heart failure patients. The design of this research uses descriptive correlational with a cross sectional approach. The population studied was CHF patients at RSUD Dr. Gunawan Mangunkusumo Ambarawa with a sample size of 34 people was taken using accidental sampling technique. Data analysis used chi square which was processed using the SPSS data processing program. Results: Family support was mostly in the good category (55.9%), medication therapy compliance was mostly in the low category (52.9%), low salt diet compliance was mostly in the low category (52.9%), the incidence of re-hospitalization was mostly in the high category. (64.7%). There was a significant relationship between family support (p-value = 0.006), adherence to medication therapy (p-value = 0.040) and low-salt diet adherence (p-value = 0.006) with the incidence of re-hospitalization. Family support, adherence to medication therapy and adherence to a low salt diet are associated with the incidence of re-hospitalization. Suggestion: CHF patients must comply with drug therapy and a low-salt diet that has been determined by showing an observation sheet at each check-up to avoid re-hospitalization   Abstrak Pasien-pasien CHF sering rawat inap ulang akibat adanya kekambuhan menyebabkan putus asa dan takut kematian. Beberapa faktor yang mempengaruhi rawat inap ulang adalah dukungan keluarga, kepatuhan terapi pengobatan dan kepatuhan diet rendah garam. Mengetahui faktor-faktor yang berhubungan dengan kejadian rawat inap ulang pada pasien gagal jantung kongestif. Desain pada penelitian ini menggunakan deskriptif korelasional dengan pendekatan cross sectional. Populasi yang diteliti pasien CHF yang pernah menjalani rawat inap ulang di RSUD Dr. Gunawan Mangunkusumo Ambarawa dengan jumlah sampel 34 orang diambil dengan teknik accidental sampling. Analisis data yang digunakan chi square yang diolah dengan SPSS. Dukungan keluarga sebagian besar kategori baik (55,9%), kepatuhan terapi pengobatan sebagian besar kategori rendah (52,9%), kepatuhan diet rendah garam sebagian besar kategori rendah (52,9%), kejadian rawat inap ulang sebagian besar kategori tinggi (64,7%). Ada hubungan yang bermakna dukungan keluarga (p-value = 0,006), kepatuhan terapi pengobatan (p-value = 0,040) dan kepatuhan diet rendah garam (p-value = 0,006) dengan kejadian rawat inap ulang. dukungan keluarga, kepatuhan terapi pengobatan dan kepatuhan diet rendah garam berhubungan dengan kejadian rawat inap ulang. Pasien CHF harus mematuhi terapi obat dan diet rendah garam yang telah ditentukan dengan menunjukkan lembar observasi setiap kali kontrol agar tidak terjadi rawat inap ulang.